Assessment of linearized buckling and nonlinear behavior of composite panels - Luciano Alves Martins (2009)
A conventional approach to the computation of critical loads of structures is to linearize the prebuckling state and to solve the resulting eigenproblem in order to obtain buckling loads as well as buckling modes. However, this approach is flawed, or extremely misleading, if in reality the prebuckling state is far from linear. Simple and useful structures, such as composite flat and cylindrical panels, have their buckling loads computed by traditional methods (linearized buckling). Nonlinear approaches are subsequently used to evaluate how realistic those linearized buckling loads are. Different stacking sequences are assessed in order to try to obtain information regarding the quality or realism of the linearized buckling loads. It is observed that for some laminates linearizing the prebuckling state leads to reasonable results. However, for other stacking sequences the results can be substantially inaccurate.